2020
DOI: 10.1111/1471-0528.16194
|View full text |Cite
|
Sign up to set email alerts
|

Atypical endometrial polyps and the incidence of endometrial cancer: a retrospective cohort study

Abstract: Objective The aim of this study was to evaluate the incidence of endometrial carcinoma, proven after hysterectomy, in patients diagnosed with atypical endometrial hyperplasia confined to a polyp. A secondary aim was to establish factors associated with (pre‐)malignant alterations in a polyp. Design A retrospective cohort study. Setting Maastricht University Medical Centre (MUMC+) and Máxima Medical Centre in Eindhoven/Veldhoven (Máxima MC). Population Women who underwent a hysteroscopic polyp resection between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
2
10
4
Order By: Relevance
“…It was found that, if EIN was detected in a polyp, concurrent malignant endometrial lesions were more likely to occur in postmenopausal or nulliparous women. Interestingly, many studies have reported that postmenopausal bleeding is associated with increased risk of neoplasia, 12–15 but neither in the present study nor in the Jacobs et al study 11 did such a relation occur. Jacobs et al 11 did not detect any prognostic factor that was related with malignancy, in the hysterectomy material of 39 polyps with atypical hyperplasia 11 .…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…It was found that, if EIN was detected in a polyp, concurrent malignant endometrial lesions were more likely to occur in postmenopausal or nulliparous women. Interestingly, many studies have reported that postmenopausal bleeding is associated with increased risk of neoplasia, 12–15 but neither in the present study nor in the Jacobs et al study 11 did such a relation occur. Jacobs et al 11 did not detect any prognostic factor that was related with malignancy, in the hysterectomy material of 39 polyps with atypical hyperplasia 11 .…”
Section: Discussioncontrasting
confidence: 86%
“…In their secondary results, they evaluated the risk of concurrent cancer risk detected in the presence of EIN in polyps. Recently, Jacobs et al 11 found the incidence of endometrial cancer in the surrounding endometrium to be 30.8% if atypical hyperplasia was detected in the polyp. This rate was similar, at 28.6%, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The risk is similar to the risk of non‐polyp‐related atypical hyperplasia, which can be up to 43% in women undergoing hysterectomy 11 . We concur with other authors that total hysterectomy is the preferred treatment for women with a diagnosis of atypical hyperplasia in a polyp 23–25 . For women with a desire for fertility or women with significant operative risks due to medical comorbidities, an alternative to hysterectomy is hysteroscopic resection.…”
Section: Discussionsupporting
confidence: 79%
“…Their studies reported that the prevalence ranges of benign hysterectomy specimens after hysteroscopic resection for atypical polyps and malignant polyps were 6.3%-34.3% and 6.7%-11.1%, respectively. [23][24][25] In contrast, our retrospective study showed that all 20 women diagnosed preoperatively with (pre-)malignant polyps had residual lesions or cancerous lesion in their hysterectomy specimens. Although six cases (30%) had normal endometrial biopsy of background endometrium, this might reflect varied accuracy of different techniques for endometrial biopsy in the detection of patients with endometrial carcinoma and atypical hyperplasia.…”
Section: Discussioncontrasting
confidence: 59%
“…If we consider endometrial cancer on an endometrial polyp, we can find that De Rijk et al showed an estimated risk of 5.6% (95% CI 0.2–17.6%) on concurrent endometrial cancer when atypia is found within an endometrial polyp [ 41 ]. The incidence of endometrial carcinoma in the surrounding endometrium after complete resection of a polyp with atypical hyperplasia is 30.8% in a more recent study [ 42 ]. This supports the advice not to change the management in this case.…”
Section: Objectivesmentioning
confidence: 99%